2021
DOI: 10.1002/cam4.3697
|View full text |Cite
|
Sign up to set email alerts
|

A novel prognostic nomogram for colorectal cancer liver metastasis patients with recurrence after hepatectomy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Although previous models have been created to predict the prognosis of stage IV CRC, these nomograms have shortcomings. Firstly, most of these studies have been conducted in relatively small populations, such as fewer than 1,000 cases in both Liang’s ( 34 ) and Beppu’s nomograms ( 35 ). Secondly, previous nomograms for the mCRC patients after liver metastases resection were presented, but the C-index was relatively low (about 0.6) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous models have been created to predict the prognosis of stage IV CRC, these nomograms have shortcomings. Firstly, most of these studies have been conducted in relatively small populations, such as fewer than 1,000 cases in both Liang’s ( 34 ) and Beppu’s nomograms ( 35 ). Secondly, previous nomograms for the mCRC patients after liver metastases resection were presented, but the C-index was relatively low (about 0.6) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leakage is one of the most serious early complications of CRC surgery and there are many publications in the literature showing that it increases mortality and morbidity in the short term, although its effects on long-term mortality are not clear (28)(29)(30)(31). On the other hand, recurrence remains one of the most important clinical problems of curative CRC resection and there are publications in the literature that it is an indicator of poor prognosis (31)(32)(33)(34) The most important limitation of our study is that it is a retrospective study. Other limitations of our study are that it is a single-center study, the limited number of patients, and heterogeneous patient characteristics due to the inclusion of patients at all CRC stages.…”
Section: Resultsmentioning
confidence: 99%
“…To an extent, the shape and growth pattern of colon carcinoma can reflect the biological characteristics of the carcinoma. [3] Postoperative pathology indicated that the cancer had invaded the serous layer (T4a). When the cancer invaded the visceral peritoneum, the cancer was able to invade the capillary venules, resulting in hematogenous metastasis.…”
Section: Pathogenesis and Metastasis Pathwaymentioning
confidence: 99%